Deregulation, competition and market integration in China's electricity sector - Guo, Xiumei; Wu, Y.; marinova, D. (Routledge, 2017)
The Routledge Handbook of Energy in Asia presents a comprehensive review of the unprecedented growth of Asian energy over the past quarter of a century.